Trapline foraging by pollinators: its ontogeny, economics and possible consequences for plants - Ohashi, Kazuharu (Oxford University Press, 2009)
BACKGROUND: Trapline foraging (repeated sequential visits to a series of feeding locations) has been often observed in pollinators collecting nectar or pollen from flowers. Although field studies on bumble-bees and hummingbirds have clarified fundamental aspects of this behaviour, trapline foraging still poses several difficult questions from the perspectives of both animals and plants. These questions include whether and how traplining improves foraging performance, how animals develop traplines with accumulating foraging experience, and how traplining affects pollen flow or plant reproduction. SCOPE: First, we review our previous work performed by using computer simulations and indoor flight-cage experiments with bumble-bees foraging from arrays of automated feeders. Our findings include the following: (1) traplining benefits foragers that are competing for resources that replenish in a decelerating way, (2) traplining is a learned behaviour that develops over a period of hours and (3) the establishment of traplines could be hampered by spatial configuration of plants such as zigzags. Second, using a simulation model linking pollinator movement and pollen transfer, we consider how service by pollinators with different foraging patterns (searchers or trapliners) would affect pollen flow. Traplining increases mating distance and mate diversity, and reduces ‘iterogamy’ (self-pollination caused by return visits) at the population level. Furthermore, increased visitation rates can have opposite effects on the reproductive success of a plant, depending on whether the visitors are traplining or searching. Finally, we discuss possible consequences of traplining for plants in the light of new experimental work and modelling. CONCLUSIONS: We suggest that trapline foraging by pollinators increases variation among plant populations in genetic diversity, inbreeding depression and contributions of floral traits to plant fitness, which should in turn affect the rates and directions of floral evolution. More theoretical and empirical studies are needed to clarify possible outcomes of such a neglected side of pollination.